Effect of Passive Tobacco Smoking Exposure on the Periodontal Status of Turkish Children - ALAN, Raif; KORKUT, Emre; GEZGİN, Onur; TÜRKOĞLU, Şükriye; ÇELİK, Esra; HALİLOĞLU, Seyfullah (Journal of Dentistry Indonesia, 2021)
Objective: This study aimed to assess the effect of passive tobacco smoking (PTS) through the comparison of the periodontal status and the C-reactive protein (CRP) and cotinine levels in the biologic fluids in children who are exposed and unexposed to PTS. Methods: A total of 148 participants, whom had smokers (PTS-exposed, n=82) and non-smokers (PTS-unexposed, n=66) in their families, respectively, were included in the study. Gingival index, plaque index, probing depth, and bleeding on probing were recorded. Moreover, saliva, urine, and gingival crevicular fluid samples were collected. CRP and cotinine levels in the biological fluids were determined by the enzyme-linked immunosorbent assay method. Results: Both groups exhibited similar values for periodontal parameters and salivary CRP levels were higher in PTS-exposed group but not significant. The mean urinary cotinine level was significantly higher in children exposed to PTS than in unexposed children. Conclusions: There was no evidence for causative role of PTS in periodontal disease in this study. Longitudinal studies including large populations should be conducted to provide stronger evidence for the causative role of PTS in periodontal disease. Also, further epidemiological studies on the social context of smoking should be performed to improve the quality of life and lifespan of the society.